PENGARUH PENGENDALIAN INTERNAL DAN KOMITMEN ORGANISASI DALAM PENCEGAHAN FRAUD PENGADAAN BARANG (STUDI KASUS PADA RSUD BENDAN KOTA PEKALONGAN) - Muhsin Hadi; Rizka Ariyanti; Muhammad Iqbal Notoatmojo (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2021)
This study aims to obtain information about internal control and organizational commitment in the procurement process at Bendan City Hospital, Pekalongan. The factors tested in this study were internal control and organizational commitment as independent variables. Meanwhile, prevention of procurement fraud is the dependent variable. This research is a research with a quantitative approach. The variables in this study consisted of Internal Control, Organizational Commitment and Fraud Prevention in Pekalongan. The population in this study were all employees at Bendan City Hospital Pekalongan. The sample in this study were employees at Bendan City Hospital Pekalongan. Data collection techniques were by giving questionnaires to employees and analyzed using multiple linear regression test with EVIEWS software version 8.1. The results of hypothesis testing show that partially the internal control variables and Organizational Commitment have a significant effect on the variable procurement fraud prevention. Meanwhile, simultaneously the independent variable, namely the internal control variable and the organizational commitment variable, is significant towards the dependent variable, namely the variable procurement fraud prevention variable.